An Explanatory Study of Green Behavior University Students in UPM And IPB University - Destrinanda, Roza; Kartika, Lindawati; Mansor, Zuraina Dato (School of Business, Bogor Agricultural University (SB-IPB), 2022)
Environmental performance in Indonesia and Malaysia, according to Yale University's Environmental Performance Index score, has decreased since 2018. Previous research has shown that collaborating with universities is one solution. UPM and IPB University have contributed to a sustainable environment as higher education institutions. Students are the largest campus community and the next future leaders. Environmental knowledge impacts green behavior. The purpose of this study was to analyze students' environmental knowledge, analyze the effect of subjective knowledge on green behavior factors, and analyze students as influencers of green behavior based on the Net Promoter Score. The number of samples used is 428 students. Data analysis was performed using descriptive analysis, PLS-SEM analysis, and Net Promoter Score. The results showed that the average value of objective knowledge of FEM IPB University students was higher than the objective knowledge of FEM UPM and combined objective knowledge. There is a positive correlation between subjective knowledge and green behavior. The NPS scores for both universities are negative, which means that student loyalty to recommending green behavior is not good. Therefore, making environmental subjects one of the compulsory subjects, requiring students to be involved in environmental projects, and encouraging students to carry out green activity projects are the best implications for creating green student behavior. Keywords: environmental knowledge, green behavior, IPB university, subjective knowledge, UPM